Penerapan Data Sains Untuk Pertumbuhan Ekonomi Berkelanjutan Dalam MSIB 6 Di PT Inovasi Lentera Cipta Kreasi - Ayyubi, Arif Rahman; Purnomo, Didit (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
Based on the Regulation of the Minister of Education and Culture of the Republic of Indonesia, number 3 of 2020 concerning National Standards for Higher Education, the Ministry of Education and Culture implements the Independent Learning Policy through the Independent Campus program which includes the Certified Independent Study and Internship (MSIB) program. Independent Campus collaborates with various industrial companies and other sectors throughout Indonesia to run the MSIB program. The purpose of this program is to provide experience, learning and opportunities for students in Indonesia to improve their skills and competencies in the world of work, so that they can adapt quickly to the demands of the times in the future. PT Inovasi Lentera Cipta Kreasi is one of the independent campus partners involved in implementing the Internship and Independent Study (MSIB) program. This company focuses on the field of data science and plays a role in developing superior human resources in information technology. This study discusses the application of data science for sustainable economic growth in the Batch 6 Independent Study program at PT Inovasi Lentera Cipta Kreasi. The research method used is Qualitative Descriptive by utilizing data, observations, researcher experiences during the Independent Study program, as well as information from books, journals and the website of the Ministry of Education and Culture. The results of the study show that the implementation of the Internship and Independent Study (MSIB) is in accordance with the Provisions of the Regulation of the Minister of Education and Culture of Indonesia number 3 of 2020 concerning National Standards for Higher Education. A total of 10 projects related to the application of science data in the MSIB program, all projects were successfully implemented.